New chalcone compound exhibits microrna-mediated anticancer properties in glioblastoma - Denis Mustafov; Shoib S. Siddiqui; Irshad Ahmad; Joanne Charlton; Jim Gkantalis; Patricia Rodriguez; Maria Braoudaki (PLoS ONE, 2025)
Background Therapy-resistant glioblastoma constitutes the most lethal adult brain malignancy, bearing extremely poor patients’ prognosis. Combinational therapies are accompanied by severe side effects and significant financial burden, highlighting the urgent need for alternative, low toxicity treatments. This study sought to investigate the therapeutic efficacy of a new synthetic chalcone molecule, SHG-44, and its cellular mechanistic actions in U87MG and U251MG glioblastoma cell line models. Methods The effect of SHG-44 on glioblastoma cell viability, clonogenic survival, and cell migration was assessed using in vitro functional assays. Cellular reactive oxygen species levels were quantified to investigate oxidative stress induced by SHG-44. The induction of apoptosis by SHG-44 was examined through nuclear fragmentation analysis and acridine orange/ethidium bromide staining. Small RNA-sequencing was performed to explore the regulatory effects of SHG44 on microRNA expression. The pharmacokinetic and pharmacodynamic properties of SHG-44 were evaluated through in-silico analysis. Results Cell viability assays demonstrated that SHG-44 significantly reduced cell viability in glioblastoma cells, with half-maximal inhibitory concentration of 70.39ΜΜ and 64.19ΜΜ in U87MG and U251MG cells, respectively. In line with these findings, a colony formation assay revealed a significant impairment of glioblastoma cells’ clonogenic survival. SHG-44 effects on cell migration demonstrated a substantial abrogation of cell migration at 100ΜΜ SHG-44 within both glioblastoma cell lines. Cellular reactive oxygen species quantification showed a significant increase of ROS at 40ΜΜ SHG-44 concentrations within U87MG cells and a non-significant elevation of ROS within U251MG cells. Nuclear fragmentation and acridine orange/ethidium bromide staining demonstrated that SHG-44 mediated cytotoxicity in U87MG and U251MG through apoptosis induction. Small RNA-sequencing analysis demonstrated that SHG-44 could regulate various cellular pathways through microRNA expression modulation in glioblastoma cell models. Further in-silico analysis of the pharmacokinetics and pharmacodynamics properties of SHG-44 demonstrated that the compound possessed sufficient absorption, distribution, potential to pass through the blood brain barrier, and low oral toxicity characteristics. Conclusion Taken together these findings suggested the potential anti-cancer properties of the newly synthesized chalcone compound, SHG-44 and its dynamic implications in glioblastoma therapeutic management.